An improved U-Net-based in situ root system phenotype segmentation method for plants - Li, Yuan; Huang, Yunlian; Wang, Mengxue; Zhao, Yafeng (Frontiers in Plant Science, 2023)
The condition of plant root systems plays an important role in plant growth and development, the Minirhizotron method is an important tool to detect the dynamic growth and development of plant root systems. Currently, most researchers use manual methods or software to segment the root system for analysis and study, this method is time-consuming and requires a high level of operation. The complex background and variable environment in soils make traditional automated root system segmentation methods difficult to implement. Inspired by deep learning in medical imaging, which is used to segment pathological regions to help determine diseases, we propose a deep learning method for the root segmentation task. U-Net is chosen as the basis, and the encoder layer is replaced by the ResNet Block, which can reduce the training volume of the model and improve the feature utilization capability; the PSA module is added to the up-sampling part of U-Net to improve the segmentation accuracy of the object through multi-scale features and attention fusion; a new loss function is used to avoid the extreme imbalance and data imbalance problems of backgrounds such as root system and soil. After experimental comparison and analysis, the improved network demonstrates better performance. In the test set of the peanut root segmentation task, a pixel accuracy of 0.9917 and Intersection Over Union of 0.9548 were achieved, with an F1-score of 95.10. The attempt of Transfer Learning for the improved network in this paper also achieved good results in the in situ root segmentation task of corn, proving that the improved network has better learning ability than before the improvement, and the improved network has good transferability.